Using archival employee data to examine retention patterns for healthcare workers in non-metropolitan Australia: a survival analysis - Priya Martin; Clara Walker; Bahram Sangelaji; Jessica Elliott; Lee O’Malley; Ansmarie Van Erp; Hwee Sin Chong; Anna Coghlan; Tony Fallon (BMC Health Services Research)
Abstract Background Healthcare workers (HCWs) play a crucial role in the delivery of much-needed healthcare services globally. Outside major metropolitan centres (i.e., non-metropolitan areas including regional, rural, remote, and very remote), recruiting and retaining HCWs continues to be a challenge. Rural Australia already faces significant healthcare challenges and inequities. Stabilizing the healthcare workforce in these underserved areas is a national priority. This study aimed to examine median retention timeframes across medicine, nursing, midwifery, and allied health professions in the public health sector in rural southern Queensland (Australia). Further, it also aimed to understand the demographic, employment, and geographical variables that influence retention of the rural healthcare workforce. Methods A 12-year administrative dataset from two public health services, servicing rural Queensland in Australia were examined. De-identified data were analyzed through descriptive statistical tests, survival analyses, and Andersen-Gill Cox proportional hazards regression. Results Data from 6651 records linked to 5527 employees were included in the analysis. Sampled employees were predominately female (70.4%), employed permanently (86.3%), in a clinical role (97.6%), and in the public hospital sector (87.5%). The overall median survival time (i.e., time employed in one location) was 1.46 years [95% CI, 1.35–1.52 years], with 41% of employees remaining in employment in location after two years. Compared to those in nursing and midwifery, those employed in medical (HR: 1.91, 95% CI: 1.75–2.09) and allied health (HR: 1.38, 95% CI: 1.26–1.51) streams were at greater risk of leaving location. This effect was relatively small, though, compared to: (a) geographic location of employment, where, compared to those working in the regional city, there was greater risk of leaving location if working in rural (HR: 1.79, 95% CI: 1.66–1.94) or remote communities (HR: 2.64, 95% CI: 2.40–2.91); and (b) employment type, where compared to being employed in permanent part-time roles, there was greater risk of leaving location if employed in casual (HR: 1.76, 95% CI: 1.56–1.99), full-time (HR: 1.65, 95% CI: 1.51–1.79) or temporary roles (HR: 2.13, 95% CI: 1.78–2.55). Conclusions Understanding retention patterns of the healthcare workforce is crucial to developing and implementing supportive interventions to enhance HCW retention in rural areas. Our findings show that the overall retention rate in this population is comparable to international evidence and may be slightly better than some previously reported rates from other Australian studies. Our findings suggest that profession, employment type, sector type, age, and geographical remoteness influenced employee retention. Further research is needed to fully explore and understand the reasons for HCWs leaving their roles and supportive measures that enable reasonable HCW retention rates.